Anthropometric characteristics and evaluation of jump and anaerobic ability of female soccer players - Vitsikanou, F.; Kotsavasileiadou, A.; Volaklis, K.; Pylianidis, Th.; Tokmakidis, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
From all the above it results that the level of the female players is in mediocre levels in comparison with the female players of abroad, a fact that may be owed to the non-systematic training of the female players since the championship that is carried out is on an amateur level with lots of breaks for the preparation of the Olympic team. The conduciveness of the anaerobic force and jump ability in soccer is very important because during the game it is required fast running, abrupt veers, jumps with intensity. The anaerobic and jump ability of female players should be improved by: Method with intervals (small and intermediate duration), Speed runnings, starts, Retrograde speed running and agility 10-5 m (Palindrome), Plyometric training (vertical and horizontal jumps with or without burden and different height). Improvement of resistance in strength.